Legal Organization for Right of Natinal Employment in Oil Contracts Between KRG and Iocs - Kayfi M. Qadr; Dhahir Majid Qadr (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The issue of employing national worker in the oil field is one of the intrusted legal topics that can be researched, as it has rarely been dealt with by researchers before. It is noticeable that the issue was subject to disagreementand a great disparity between the views of the jurists and even in the content ofoil contracts, as well as the laws related to the subject, as some countries have focused a lot on employing the largest possible number of national workers in the oil field, especially in decision posts that have direct effect on the oil policy in the country, while there are countries that did not pay much attention to the issue and relied on the contractual relations concluded between them and forigion oil companies. Therefore, this research is a legal attempt to clarify the positions of the laws of the oil countries and their oil contracts with forigion oil companies regarding the interest in the right to employment for national workers on the one hand, and to suggest the best solutions to solve the legal problems resulting from the lack of interest in the subject, especially in the future. The research is divided into two sections. In the first setion we have dealt with the definition of employment in the oil field in general and explained the point of views of the oil country lagislations in question and the oil contracts concluded between them and foreign oil companies on the topic. Wile in the second topic, we focused on national plans to increase the number of national workers in the oil sector. Especially in High decision posts. At the end of the research, we reached a set of conclusions and recommendations on the topic. One of the most important conclusions is that the view of the laws in question are different on how to deal with the issue of employing the national worker in the field of oil, and we found out that the view of Nigerian lagislation was better than others in terms of its regulation of this topic. Being involved in organizing the details of the provisions on the subject. One of the most important recommendations that we put forward at the end of the research is that it is necessary to make an amendment in the oil and gas law in the region regarding setting a certain percentage for the employment of national workers in the field of oil and imposing that on foreign oil companies operating in the region and not leaving this important matter to the interests of these companies.